Protection from age-related increase in lipid biomarkers and inflammation contributes to cardiovascular protection in Gilbert's syndrome - Wallner, Marlies; Marculescu, Rodrig; Doberer, Daniel; Wolzt, Michael; Wagner, Oswald; Vitek, Libor; Bulmer, Andrew C.; Wagner, Karl-Heinz (Clinical science (1979), 2013)
Recent epidemiological and clinical data show protection from CVD (cardiovascular disease), all-cause mortality and cancer in subjects with GS (Gilbert's syndrome), which is characterized by a mildly elevated blood bilirubin concentration. The established antioxidant effect of bilirubin, however, contributes only in part to this protection. Therefore we investigated whether mildly elevated circulating UCB (unconjugated bilirubin) is associated with altered lipid metabolism. The study was performed on GS and age- and gender-matched healthy subjects (n=59 per group). Full lipoprotein profile, TAG (triacylglycerols), Apo (apolipoprotein)-A1, Apo-B, lipoprotein(a), the subfractions of LDL (low-density lipoprotein) and selected pro-inflammatory mediators were analysed. A hyperbilirubinaemic rodent model (Gunn rats, n=40) was investigated to further support the presented human data. GS subjects had significantly (P<0.05) improved lipid profile with reduced total cholesterol, LDL-C (LDL-cholesterol), TAG, low- and pro-atherogenic LDL subfractions (LDL-1+LDL-2), Apo-B, Apo-B/Apo-A1 ratio and lower IL-6 (interleukin 6) and SAA (serum amyloid A) concentrations (P=0.094). When the control and GS groups were subdivided into younger and older cohorts, older GS subjects demonstrated reduced lipid variables (total cholesterol and LDL-C, TAG and LDL-C subfractions, Apo-B/Apo-A1 ratio; P<0.05; Apo-B: P<0.1) compared with controls. These data were supported by lipid analyses in the rodent model showing that Gunn rat serum had lower total cholesterol (2.29±0.38 compared with 1.27±0.72 mM; P<0.001) and TAG (1.66±0.67 compared with 0.99±0.52 mM; P<0.001) concentrations compared with controls. These findings indicate that the altered lipid profile and the reduced pro-inflammatory status in hyperbilirubinaemic subjects, particularly in the older individuals, probably contribute additionally to the commonly accepted beneficial antioxidant effects of bilirubin in humans.